2022
DOI: 10.1177/00469580221090408
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Behavioral Interventions on Patient Activation in Adults with Hypertension: A Systematic Review and Meta-Analysis

Abstract: Introduction: Behavioral interventions assist patients in maintaining optimal self-management of their health, especially in those at risk of certain conditions. Little is known about the effects of self-management interventions on patient activation in adults with hypertension. Therefore, this systematic review and meta-analysis aimed to evaluate how self-management strategies affect changes in activation levels in adults with hypertension. Methods: We searched online databases: PubMed, CINAHL, and Cochrane C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Innab and Kerari conducted a systematic review and meta-analysis aimed to evaluate how self-management strategies affect changes in activation levels in adults with hypertension. 28 As a result, the authors only found four randomised controlled trials that assessed the effects of self-management interventions on patient activation in adults with hypertension. Self-management interventions (ie, community-based self-management programmes, motivational interviewing strategies) were associated with better PAM scores and BP control than usual care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Innab and Kerari conducted a systematic review and meta-analysis aimed to evaluate how self-management strategies affect changes in activation levels in adults with hypertension. 28 As a result, the authors only found four randomised controlled trials that assessed the effects of self-management interventions on patient activation in adults with hypertension. Self-management interventions (ie, community-based self-management programmes, motivational interviewing strategies) were associated with better PAM scores and BP control than usual care.…”
Section: Discussionmentioning
confidence: 99%
“…Self-management interventions (ie, community-based self-management programmes, motivational interviewing strategies) were associated with better PAM scores and BP control than usual care. 28 More research needs to be conducted aimed at evaluating the impact of patient activation on chronic disease self-management in Middle Eastern countries. In the context of hypertension disease, targeted strategies tailored to individual levels of activation are needed to improve self-management skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-sectional analyses in primary care have demonstrated increased patient activation as associated with reduced probability of ED visits, hospitalization, obesity, and smoking, along with increased likelihood of up to date status of age-appropriate cancer screening, normal blood pressure, and lipid laboratory markers [ 48 ]. Patient engagement is feasible, effective, and relevant in chronic medical conditions such as hypertension [ 49 ], diabetes [ 50 ], and heart failure [ 51 ]. In PwMS, higher patient activation is associated with improved depressive symptoms, quality of life, self-efficacy, and fatigue [ 46 , 52 , 53 ] as well as greater confidence in selecting disease modifying therapies in partnership with their MS healthcare providers [ 54 ].…”
Section: Discussionmentioning
confidence: 99%